DEPICTION OF FEMINISM CONCEPT IN DISNEY ANIMATED MOVIE: ENCANTO 2021 - Salamina, Lugina Ayu; Tawami, Tatan (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
This paper is entitled